Proceedings of the 2017 2nd International Conference on Financial Innovation and Economic Development (ICFIED 2017) 2017
DOI: 10.2991/icfied-17.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Hijab Fashion Consciousness and Consumption Among Generations X and Y

Abstract: Abstract. Marketers believe that they should treat generations X and Y as two different market segments, including when they offer a fashion product. Islam has strict laws regarding women's fashion: All women should cover their head and body using a veil or hijab regardless of their cohort or age. This study aims to examine the influence of cohort on hijab fashion-related attitude and consumption behaviour. The study finds no significant differences between generations X and Y in terms of dressing style, sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The chemicals like sodium hydroxide and carbon disulphide are used in making polyester fibers which are derived from crude oil, gasoline or coal. In this fashion world where there is a cut throat competition, modest fashion sector has made a soft entry into the design business through hijabs and Abayas [17]. This change in the industry has been accepted by the consumers of modest fashion in a responsive manner and they took quick actions in experimenting new designs and fabrics which can be used in the modest world ( Fig.5).…”
Section: Fig4 Structure Of Polymersmentioning
confidence: 99%
“…The chemicals like sodium hydroxide and carbon disulphide are used in making polyester fibers which are derived from crude oil, gasoline or coal. In this fashion world where there is a cut throat competition, modest fashion sector has made a soft entry into the design business through hijabs and Abayas [17]. This change in the industry has been accepted by the consumers of modest fashion in a responsive manner and they took quick actions in experimenting new designs and fabrics which can be used in the modest world ( Fig.5).…”
Section: Fig4 Structure Of Polymersmentioning
confidence: 99%
“…In addition, respondents felt that by wearing fashionable hijabs, it would serve as an encouragement to the non-wearers to start donning a hijab due to it not being old and traditional. Hasna and Hati (2017), research found that factors that influence donning fashionable hijab are dressing style as well as knowledge about fashion industry. Furthermore, income too factored in one's decision to wear fashionable hijab.…”
Section: Research Objectivementioning
confidence: 99%